PROTECTIVE EFFECT OF AQUEOUS EXTRACT OF LEAVES OF MURRAYA KOENIGII, AGAINST ALUMINUM CHLORIDE-INDUCED OXIDATIVE STRESS IN RAT LIVER AND KIDNEY - REDDY B, MAHESWARI; CK, DHANAPAL; BVS, LAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the current study was to investigate the hepatoprotective, nephroprotective, and cholesterol-lowering activity of aqueous extract of Murraya koenigii (MK) leaves against AlCl3-induced oxidative stress in rats. Methods: Wistar albino rats were distributed into six groups (6 each). Group I (control), and Group II administered with distilled water, and aluminum chloride (AlCl3), (40 mg/kg body weight [b.w], oral), respectively. Group III rats were treated with standard Vitamin E (100 mg/kg b.w, p.o) and AlCl3 (40 mg/kg b.w, oral). Group IV, V, and VI received aqueous extract of leaves of Murraya koenigii (AEMK) (100 mg/kg b.w, peroral [p.o], 200 mg/kg b.w, p.o, and 400 mg/kg b.w, p.o), respectively, for a period of 35 days. Results: Histopathological examination was observed deformities in hepatic and renal tissues due to aluminum exposure which augment the aforementioned results. Coadministration of AEMK along with Al significantly restored the serum biomarkers to their near-normal levels and has the ability to overcome Al-induced oxidative stress, manifested by a significant reduction in hepatic and renal malondialdehyde level. It increased cellular antioxidant defense, particularly by increasing GPx, glutathione, GR, and catalase levels, preserved normal hepatic and renal histological architecture. Conclusion: It could be concluded that AEMK has significant radical scavenging activity and can mop up Al-induced toxicity, suggesting hepatoprotective and nephroprotective potential.